Depression and suicidal risk among pharmacy students at Srinakharinwirot University - เชื้อมงคล, วรรณคล; รุ่งรัตนพงษ์พร, ปรีดา; ฉันทะธัมมะ, สุรพงศ์ (Journal of Medicine and Health Sciences, 2018)
This cross-sectional descriptive study aim to explore the prevalence of depression and suicidal risk and to evaluate self-esteem of pharmacy students at Srinakharinwirot University. Data were collected using the questionnaires including general characteristics, the Thai version of Center for Epidemiologic Studies-Depression scale (CES-D), a suicidal risk screening test of Tangseree, et al, and the self-esteem evaluation of Rosenberg. A total of 349 out of 490 pharmacy students (71.2%) participated in this study. The results showed that the prevalence of depression and suicidal risk were 27.2% and 35.0%, respectively. Most participants (57.2%) had high level of self-esteem.